OCA/OCP Java SE 7 programmer I & II study guide (exams 1Z0-803 & 1Z0-804) - Sierra, Kathy (McGraw-Hill Education, 2015)
Prepare for the OCA/OCP Java SE 7 Programmer I and II exams with this exclusive Oracle Press guide. Chapters feature challenging exercises, a certification summary, a two-minute drill, and a self-test to reinforce the topics presented. Topics include: declarations and access control; object orientation; assignments; operators; strings and arrays; flow control and exceptions; assertions and Java 7 exceptions; string processing, data formatting, and resource bundles; I/O and NIO; advanced OO and design patterns; generics and collections; inner classes; threads; concurrency; Java Database Connectivity (JDBC). --